2003
DOI: 10.1055/s-2003-38897
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis during Normal Pregnancy and Puerperium

Abstract: During normal pregnancy the hemostatic balance changes in the direction of hypercoagulability, thus decreasing bleeding complications in connection with delivery. The most important initial factor for acute hemostasis at delivery is, however, uterine muscle contractions, which interrupt blood flow. Global tests such as Sonoclot signature, the Thromboelastogram, and a new method analyzing overall plasma hemostasis, all show changes representative of hypercoagulability during pregnancy. Increased endogenous thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
285
2
19

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(329 citation statements)
references
References 40 publications
(60 reference statements)
17
285
2
19
Order By: Relevance
“…The changes in fibrinogen concentration may be related to pregnancy and delivery. It is known that during pregnancy the activation of blood coagulation panel takes place, and these changes in blood coagulation system, including fibrinogen concentration, are normalized within one month after delivery (Hellgren 2003). In our study the highest concentrations of fibrinogen were observed in cows just before calving.…”
Section: Discussionsupporting
confidence: 49%
“…The changes in fibrinogen concentration may be related to pregnancy and delivery. It is known that during pregnancy the activation of blood coagulation panel takes place, and these changes in blood coagulation system, including fibrinogen concentration, are normalized within one month after delivery (Hellgren 2003). In our study the highest concentrations of fibrinogen were observed in cows just before calving.…”
Section: Discussionsupporting
confidence: 49%
“…Frequency of gestational thrombocytopenia was estimated to be 7-12% at term [12,14,15]. A platelet count of 80 x 10 9 /L is considered to be a safe threshold [20] with no impact on either mother [21] or the fetus [15], unless the thrombocytopenic mother has some comorbids [14]. Mothers having platelet count of 150 x 10 9 /L at 28 th week of gestation have a pre-birth platelet count >100…”
Section: Quantitative Changes In Plateletsmentioning
confidence: 99%
“…As a result, an increase in mean platelet volume (MPV), platelet distribution width and large-size platelets in peripheral film were observed in many [7,9,17,25] but not all reports [18,26]. Large-sized platelets may be pathogenic [27] but since platelet turnover is usually normal [20] and platelet count is low therefore, overall effect is a balanced platelet mass [7]. Usually, the platelet count normalizes within 4-6 weeks after delivery [20].…”
Section: Quantitative Changes In Plateletsmentioning
confidence: 99%
“…Elevated plasma levels of clotting factors (such as fibrinogen and thrombin), and reduced anticoagulants (such as protein S, activated protein C, and antithrombin III), are reported to occur during pregnancy (James, 2009;Patil et al, 2013). In addition, fibrinolysis is impaired by an increase in PAI-1 and PAI-2, the latter synthesized from the placenta, with a net result tilting toward thrombotic state (Hellgren, 2003;Patil et al, 2013).…”
Section: Venous Thrombosis During Pregnancymentioning
confidence: 99%
“…Similarly, high levels of estrogen with the use of oral hormone contraceptives or hormone therapy augment the increase in the levels of factor VII, VIII, and X, prothrombin, and fibrinogen (Hellgren, 2003). Multiple mechanisms that activate thrombotic processes and mediators in the endothelium are considered to be amplified during pregnancy.…”
Section: Venous Thrombosis During Pregnancymentioning
confidence: 99%